RETRACTED: Unlocking employee creativity: How learning orientation and transformational leadership spark innovation through creative self-efficacy - Chiqing Qian; Daisy Mui Hung Kee; Biao Zeng; Hala Najwan Sabeh (PLoS ONE, 2025)
This study explores the mechanisms through which individual learning orientation (ILO) and transformational leadership (TL) foster employee creativity, with a particular focus on the mediating role of creative self-efficacy (CSE) within small and medium-sized enterprises (SMEs) in China’s manufacturing sector. Drawing on a sample of 406 employees, the study employs hierarchical linear modeling (HLM) to analyze the multi-level influences on creativity. The findings indicate that ILO significantly enhances employee creativity, underscoring the importance of continuous personal development and proactive learning in innovation processes. All four dimensions of TL—idealized influence (II), inspirational motivation (IM), intellectual stimulation (IS), and individualized consideration (IC) — are positively associated with employee creativity. CSE is found to mediate the relationship between ILO and creativity, as well as between II, IS, IC, and creativity, although it does not mediate the effect of IM. These results highlight the pivotal role of CSE as a cognitive mechanism through which leadership and learning orientations translate into creative outcomes. The study contributes to the literature on workplace creativity by integrating individual and leadership factors, with psychological resources. Practical implications for SME managers include the cultivation of supportive leadership practices and the promotion of learning-oriented cultures to enhance creative performance. The paper concludes with recommendations for future research directions.